2013
DOI: 10.1016/j.ejvs.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Histologically Unstable Asymptomatic Carotid Plaques Have Altered Expression of Genes Involved in Chemokine Signalling Leading to Localised Plaque Inflammation and Rupture

Abstract: The findings confirm the intuitively held belief that changes in chemokine and protein signalling may be associated with acute plaque disruption and precede the onset of symptoms. Once validated, these genes could therefore become targets for innovative medical treatments in the future or could help identify asymptomatic patients with histologically unstable plaques that would benefit from surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…50 However, little is known about the role of CD137 in advanced atherosclerosis, and it is plausible that the protein levels are downregulated immediately after plaque rupture because it has been suggested that rapid changes in the expression of genes and proteins can cause variations in plaque stability. 51 Of note, a tendency toward increased staining in symptomatic lesions was observed for most other proteins studied here, although not reaching significance levels in our semiquantitative analyses. This indicates some limitations of our study; however, we anticipate that by including more patients in TMAs and quantifying with a finer grading-scale, small changes in protein expression levels may also be detected.…”
Section: Discussionmentioning
confidence: 77%
“…50 However, little is known about the role of CD137 in advanced atherosclerosis, and it is plausible that the protein levels are downregulated immediately after plaque rupture because it has been suggested that rapid changes in the expression of genes and proteins can cause variations in plaque stability. 51 Of note, a tendency toward increased staining in symptomatic lesions was observed for most other proteins studied here, although not reaching significance levels in our semiquantitative analyses. This indicates some limitations of our study; however, we anticipate that by including more patients in TMAs and quantifying with a finer grading-scale, small changes in protein expression levels may also be detected.…”
Section: Discussionmentioning
confidence: 77%
“…Modest alterations in gene expression levels were found in plaques and PBMCs from S and AS patients, probably because these two groups represent entities of the same underlying disease [14,46]. Despite a reduction in sample size and statistical power, we also compared gene expression between different subgroups of patient phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This restricts the generalization of the present results to high-risk populations with end-stage disease. It is most likely that the phenotyping of patients based on the presence or absence of cerebral symptoms was insufficient to completely exclude overlap between the groups, as lesions from AS patients may vary with regard to morphological features of plaque instability [46]. Unfortunately, histological plaque classification [70] was incompatible with the sampling protocol used here.…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerable plaques are associated with thin fibrous caps, large lipid cores, intraplaque hemorrhage, inflammation (Stary et al 1995; Fleiner et al 2004; Salem et al 2013; Marnane et al 2014; Salem et al 2014), and in some reports calcification (Shaalan et al 2004). Ultrasound methods used to assess carotid plaque for features of vulnerability include; integrated backscatter (IBC) (Bridal et al 2000; Kawasaki et al 2001; Nagano et al 2008), midband, slope and intercept values of straight-line fit (MBF) to the apparent backscatter transfer function, (Waters et al 2003) carotid strain imaging, (Maurice et al 2005; Shi et al 2008; Shi et al 2009; Wang et al 2013; Wang et al 2016a; Wang et al 2016b), acoustic radiation impulse force imaging (ARFI) based approaches (Czernuszewicz et al 2015), shearwave elastography (Garrard et al 2015) and grayscale analyses of plaque features (El-Barghouty et al 1996; Tegos et al 2000; Grogan et al 2005; Salem et al 2014).…”
Section: Introductionmentioning
confidence: 99%